Development of the Reading Comprehension Strategies Questionnaire (RCSQ) for late elementary school students - Bogaert, Rielke; Merchie, Emmelien; Rosseel, Yves; Van Keer, Hilde (Frontiers in Psychology, 2023)
Late elementary education constitutes a critical period in the development of reading comprehension strategies, a key competence in today’s society. However, to date, appropriate measurements to map late elementary students’ reading strategies are lacking. In this respect, the present article first describes the development and validation of the 26-item Reading Comprehension Strategies Questionnaire (RCSQ). To this aim, exploratory (sample 1: n = 1585 students) and confirmatory (sample 2: n = 1585 students) factor analyses were conducted. These analyses resulted in the RCSQ, consisting of five subscales: 1) overt cognitive reading strategies, 2) covert cognitive reading strategies, 3) monitoring, and 4) evaluating. For non-native and bilingual students, a fifth subscale ‘using home language in view of comprehending texts’ emerged. Second, multilevel analyses were performed to explore individual differences in late elementary students’ reading comprehension strategy use. Implications for practice and future research are discussed.